A new class of composite indicators for measuring well-being at the local level: An application to the Equitable and Sustainable Well-being (BES) of the Italian Provinces. (May 2017) - Ciommi, Mariateresa; Gigliarano, Chiara; Emili, Alessandra; Taralli, Stefania; Chelli, Francesco Maria
Abstract: The aim of this paper is to propose a class of composite indicators for measuring well-being at the local level, which takes into account the variability between and within the local units. Although we believe that well-being is a multidimensional concept and cannot be reduced to a single measure, we also stress the importance of aggregating the information of several well-being indicators into a reduced number of composite indicators, one for each well-being domain, which play a crucial role in policymaking and benchmarking. As an application, we focus on the Equitable and Sustainable Well-being of the Italian Provinces. In particular, based on a dataset containing 41 elementary indicators, we aggregate them by domain, comparing different aggregative approaches and illustrating the difference in the rankings of the Italian Provinces they produce. Finally, as an illustrative example, we focus on a member of the class of composite indicators that accounts both for vertical variability (between the Provinces) and horizontal variability (within the Provinces). The construction of a composite index for each domain allows us to evaluate and compare multidimensional well-being among the Italian Provinces.